2018
DOI: 10.1172/jci96429
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of nonlipidated, aggregated apoE with antibodies inhibits amyloid accumulation

Abstract: The apolipoprotein E E4 allele of the APOE gene is the strongest genetic factor for late-onset Alzheimer disease (LOAD). There is compelling evidence that apoE influences Alzheimer disease (AD) in large part by affecting amyloid β (Aβ) aggregation and clearance; however, the molecular mechanism underlying these findings remains largely unknown. Herein, we tested whether anti-human apoE antibodies can decrease Aβ pathology in mice producing both human Aβ and apoE4, and investigated the mechanism underlying thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 41 publications
7
101
0
Order By: Relevance
“…This finding provides a mechanistic explanation to the observed formation of more amorphous assemblies here shown by TEM and also a possible route of formation to the circulating complexes between ApoE and Aβ found in vivo . Inhibiting ApoE binding may also provide a mechanistic explanation to the recent findings where a beneficial effect is observed after injection of anti‐ApoE4 antibodies into AD mouse model as well as peptides having the ability to interfere with the ApoE‐Aβ interaction .…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…This finding provides a mechanistic explanation to the observed formation of more amorphous assemblies here shown by TEM and also a possible route of formation to the circulating complexes between ApoE and Aβ found in vivo . Inhibiting ApoE binding may also provide a mechanistic explanation to the recent findings where a beneficial effect is observed after injection of anti‐ApoE4 antibodies into AD mouse model as well as peptides having the ability to interfere with the ApoE‐Aβ interaction .…”
Section: Introductionsupporting
confidence: 63%
“…Although the involvement of ApoE in the process of AD is a multifactorial process, these findings might present an explanation for the beneficial effect noted from ApoE knockout studies where ApoE rather is suggested to be a pathological chaperone. Inhibiting ApoE binding may also provide a mechanistic explanation to the recent findings where a beneficial effect is observed after injection of anti‐ApoE4 antibodies into AD mouse model . Based on these results, interfering with ApoE binding and its ability to prevent elongation might reduce a population of potentially more toxic Aβ assemblies and serve as an interesting therapeutic target.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, apoE KO AD mice have reduced amyloid deposition (Bales et al 1997;Irizarry et al 2000) and tau pathology (Shi et al 2017). Furthermore, immunotherapy against apoE was associated with reduced Ab deposition in AD mice (Kim et al 2012), an effect that has recently been recapitulated using an antibody targeting only non-lipidated forms of apoE (Liao et al 2018). These findings, together, indicate that the lipidation state of apoE may influence AD pathology more so than the absolute level of apoE.…”
Section: Discussionmentioning
confidence: 95%
“…), an effect that has recently been recapitulated using an antibody targeting only non‐lipidated forms of apoE (Liao et al . ). These findings, together, indicate that the lipidation state of apoE may influence AD pathology more so than the absolute level of apoE.…”
Section: Discussionmentioning
confidence: 97%
“…Two of the running Alzheimer's programs target BACE1-an aspartic protease that initiates the formation of Ab from APP-and TREM2, an immune receptor found in brain microglia that has been linked to the risk of developing Alzheimer's. Moreover, a recent study resulting from a collaboration between Denali and Washington University School of Medicine in St Louis, MS, USA, showed that an antibody targeting the apoE protein found in brain plaques cuts the level of plaques by half, raising hopes that this could limit the debilitating symptoms of the disease [5]. The researchers expressed the human APOE gene-variants of which are considered the most significant risk factor for AD-in APOE-knocked mice.…”
Section: Biotech Picking Upmentioning
confidence: 99%